Understanding the Asal of young Filipino first-time voters in polymedia environments - Garganera, Mary Cielou B.; Sangalang, Luise Gayle C.; Rapanot, Czekainah Esrah S. (Quezon City College of Mass Communication, University of the Philippines, 2023)
The proactive participation of the Filipino youth in socio-civic and political activities has continuously made such a significant presence in both on-ground and online spaces. The 2022 Philippine elections is a recent political event that has driven more youth to participate in political discourses on multiple media platforms. The youth's mediated interactions during the election season provide an opportunity to investigate how their asal manifests in a digital environment, especially when they converse with older people. Hence. this study looked into how Filipino youth first-time voters embody Filipino core values of asal when they have political discussions with their older family members in polymedia environments. To achieve this, Madianou and Miller's (2012) Polymedia Theory and Jocano's (1993) Filipino Value System serve as the theoretical anchors of the study. Data were collected through in-depth interviews with a total of 15 Filipino youth first-time voters as informants. The findings showed that the youth's perceived roles as voters, generational differences, and their emotions all contribute to their media choices and polymedia practices. They utilize platform affordances to communicate with others, express themselves, and share information about politics and the elections. Norms of kapwa, damdannn, and dangal manifested in the polymedia practices of the young first-time voters as they managed their political discussions with their older family members.
Vita.
Thesis
Includes bibliographical references (pages 98-117) and appendices (pages 118-132).
Keywords: Student movements -- Philippines; Internet and activism -- Philippines; Political activists -- Philippines